The Impact of Implementing E-Services on Rationalizing Spending in Syria A Study of Ministries Using E-Services in Their Transactions (Journal of Hama University, 2026)
The research aimed to shed light on the impact of e-services on public spending in ministries that use e-services in their transactions in Syria. The current study demonstrated the importance of e-services in Syria through a study of some ministries that use e-services in their transactions and their impact on public spending.In general, the study proved that electronic services in some government ministries in Syria contributed to reducing government spending.The descriptive analytical approach was used, relying on official data from the Ministries of Higher Education and Scientific Research, the Interior, Education, Finance, Health, and public banks in Syria. The SPSS statistical program was used to analyze this data, and regression analysis was applied to determine the relationship between the dependent and independent variables.Among the most important findings of this study were:-The electronic transactions provided by the Ministry of Interior, Ministry of Education, Ministry of Health, and public banks lead to a decrease in government spending.-The electronic transactions provided by the Ministry of Higher Education and Scientific Research are increasing government spending.-The weak electronic infrastructure at the Ministry of Finance prevents it from making an effective contribution to reducing government spending. Keywords: Digital transformation, e-services
Keywords: Keywords: Digital transformation, e-services